Viability of Annuity-based Option as Retirement form of Benefit among EPF Retirees - Hazimi Mohammed Foziah, Nik; Liza Ghazali, Puspa; Mamat, Mustafa; Salleh, Fauzilah; Ansyari Guci, Dede; Arni Syed Jaaffar, Sharifah; Sadad Mahmud, Mohd; Shukri Yazid, Ahmad (International Journal of Engineering and Technology, 2018)
Most of the countries nowadays has experiencing an ageing population. This could be a serious threaten for those who lack of financial preparation towards retirement. In Malaysia, majority of the private sector workforceâ€™s retirees had depleted their retirement savings just within 3 to 5 years. Lack of financial management can be a great problem that leads to the poor elderly population, as life expectancy of Malaysian people in the age of 65 for male and female can live for 15 and 17 years old respectively. Therefore, the substitute of annuity-based scheme from a popular lump-sum retirement benefit among EPF retirees would be an ideal to overcome the issues. Therefore, the study examined whether the annuity-based option retirement benefit could sustain their financial position for at least 20 yearsâ€™ period. Â Through mathematical simulation and analysis, the study found that by choosing annuity based as retirement form of benefit by EPF members, they can receive a monthly annuity payment for 15 yearsâ€™ period. Therefore, this will be a good indicator for the authority to revise the retirement system and implement the annuity-based option as a mandatory in order to keep elderly out of poverty line. Â Â